FEATURES OF INHERITANCE BY LAW: COMPARATIVE LEGAL ANALYSIS - Nukusheva, Aigul Ashimovna; Kuandykov, Bakhytzhan Zhursunovich; Zhailau , Zhanat (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
In the conditions of modern society, inheritance law is becoming the subject of increasingly active study and analysis. In the context of the transition of the Republic of Kazakhstan to a market economy, the implementation of socio-economic reforms and the development of information technology, the issues of inheritance law acquire new aspects and challenges. In this regard, this study is aimed at conducting a comparative analysis of the features of inheritance by law both in the Republic of Kazakhstan and in other countries, in order to identify similarities and differences in the legal regulation of this area. The purpose of the study is to study the key aspects of inheritance law using a comparative legal approach. Within the framework of this study, several main tasks have been identified: first, to analyze the legislation regulating inheritance by law in the Republic of Kazakhstan and in other countries of the world. This stage includes the study of the basic rules and principles governing the inheritance process in various legal systems. Secondly, to determine the circle of persons who have the right to inherit by law both in the Republic of Kazakhstan and in foreign countries. This important study will reveal differences in the established categories of heirs and the legal basis for their succession. Thirdly, to conduct a comparative analysis of the legal regulation of heirs by law in the civil law of the Republic of Kazakhstan and similar norms in foreign countries. This stage of the analysis will reveal similarities and differences in legal approaches to inheritance and its consequences for heirs. The results of the study are supposed to be used as a basis for developing recommendations for improving inheritance legislation, as well as for a deeper understanding and application of inheritance rules both in the Republic of Kazakhstan and in other countries. Thus, the study has practical significance and can contribute to improving the legal regulation of inheritance relations, ensuring a more equitable and effective succession procedure.